O real em sua fabulação : a herança nietzscheana na hermenêutica filosófico-religiosa de Gianni Vattimo - Uliana, Marcony Brandão (2011)
This work addresses the Nietzschean legacy in Gianni Vattimos philosophical and religious hermeneutics.This approach will be undertaken by following the thread of the Nietzschean understanding of the fabulation of the real and its implications in postmodern discourse ethics. We present as a fundamental characterization, to be outlined in the first chapter, the critique of the categories of modernity that are addressed to subjectivity and historicism, beyond its egress in art (with notions of the Dionysian and Apollonian).This egression will be carried out by tracing the nihilistic aspect of the will of power, namely its deconstructive capacity, finding a more successful form in the emancipatory project of the "beyond-the-human", at the core of which is decision-making as a moment of accepting responsibility. The second chapter will look at the relationship between secularization and Christianity and the role to be played by Christianity in the mediation of accomplished with caritas, in the Age of cultural conflicts, through caritas, in the Age of Interpretation. The third and final chapter will analyze the link between the understanding of the fabulation of the real at its nihilistic heart, and the characterization of a post-metaphysical ethics discourse.